A “Pura Vida” Summer in Costa Rica - Allen, Hailie (Journal of International Students, 2011)
Upon returning to the Memphis airport on the third of July 2011, having been out of the country for a month, the thirteen other students from Arkansas State University and I were exhausted, ready to see our loved ones, and to eat anything other than rice and beans. It was a bittersweet feeling to be home. We had just completed a study abroad program in the extraordinarily beautiful country of Costa Rica.